Parameters of labile organic carbon as the indicators of the stability of soil organic matter under different land use - Erika Balontayová; Juraj Hreško; Viera Petlušová; Peter Petluš; Bożena Dębska; Tomáš Lošák (Soil and Water Research)
The labile fractions of organic carbon (OC), which are a reflection of the properties of soil and its use, appear to be suitable parameters for their use as indicators. The aim of this study was to determine the reliable and relatively simple indicators for detecting the chemical and physical stabilizations of OC, which would respond sensitively to land use. The study includes forest ecosystem (FE) and agroecosystem (AE) with different tillage intensities (reduced tillage, RT and conventional tillage, CT) on real farms. Parameters of the labile C and N were tested. For a depth of < 0.1 m in the FE, the hot water extractable organic carbon (HWEOC) for chemical stabilization and labile nitrogen (NL) for physical stabilization appear as the most suitable indicators. Higher values of HWEOC indicate the OC stabilization by decreasing decomposition, pH or by increasing carbonates, recalcitrant fractions, and higher values of NL by OC incorporation into the silt fraction and larger macro-aggregates. In the AE with RT, these are the HWEOC for chemical stabilization and carbon pool index (CPI) or index of carbon lability (LIC) for physical stabilization. Higher values of CPI and LIC indicate the stabilization by the formation of size-optimal dry-sieved (DSA; 1-3 mm) and wet-sieved (WSA; 1-2 mm) soil aggregates. In the AE with CT, it was the NL. Its higher values point to the stabilization through the carbonates, alkaline cations, size-fraction of > 0.01 mm and the formation of DSA (1-3 mm). For a depth of < 0.3 m in the AE, these are the CL (for RT), higher value of which points to the stabilization by clay and alkaline cations, and HWEOC (for CT), higher value of which indicates the stabilization in the conditions of the soil acidification.